Venita Fields : what private equity professionals really do - Collins, Derrick, (SAGE Knowledge. Cases., 2017)
Ever since he had heard her speak at a private equity conference, Babatunde Omotoba had wanted to work for Venita Fields, co-founder and senior managing director of private equity firm Smith Whiley & Company. He wrote and asked her for an informational interview, and was excited to receive her invitation to meet with her at the firm's regional office in Evanston, Illinois. After the interview, however, Omotoba came to the grim realization that despite all his preparationsresearching private equity firms, studying the types of deals they make, and evaluating the analytical tools used to perform due diligence on companies and make investment decisionshe did not have a full grasp on the actual day-to-day work private equity professionals perform. He spent time reviewing materials from the career management office about private equity, and he meets two Kellogg alumni for informational interviews. He also reviews the investment process. The case ends with Omotoba having a broader perspective on the human aspect of private equity, beyond the analytical and financial aspects, as he anticipates meeting Fields again, hopefully to get the job offer.